2014
DOI: 10.3109/10717544.2014.891270
|View full text |Cite
|
Sign up to set email alerts
|

Role of lipid-based excipients and their composition on the bioavailability of antiretroviral self-emulsifying formulations

Abstract: The objective of this study was to develop self-emulsifying drug delivery system (SEDDS) to improve solubility and enhance the oral absorption of the poorly water-soluble drug, nevirapine. This lipid-based formulation may help to target the drug to lymphoid organs where HIV-1 virus resides mainly. The influence of the oil, surfactant and co-surfactant types on the drug solubility and their ratios on forming efficient and stable SEDDS were investigated in detail. Two SEDDS (F1 and F2) were prepared and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
0
14
0
2
Order By: Relevance
“…Better in vivo absorption in the presence of Tween 80 ascribed to the possible inhibition of efflux transport and increased lymphatic transport. In another research, the presence of higher concentration of Tween 80 (56.4%) and lower concentration of oil (Caprylic acid; 20%) in a SEDDS of Nevirapine resulted in better ex vivo intestinal permeability as well as better C max and AUC 0-t compared to the SEDDS containing lower Tween 80 (46.8%) and higher oil (20%), although both formulations resulted better oral bioavailability in rats than marketed suspension (Chudasama et al, 2015). From all these discussed studies, it can be concluded that the in vitro models, undoubtedly can give idea about drug absorption through the intestine, but in vivo studies are essential to find out the exact outcome of the delivery system.…”
Section: Correlation Between In Vitro Model and In Vivo Studiesmentioning
confidence: 99%
“…Better in vivo absorption in the presence of Tween 80 ascribed to the possible inhibition of efflux transport and increased lymphatic transport. In another research, the presence of higher concentration of Tween 80 (56.4%) and lower concentration of oil (Caprylic acid; 20%) in a SEDDS of Nevirapine resulted in better ex vivo intestinal permeability as well as better C max and AUC 0-t compared to the SEDDS containing lower Tween 80 (46.8%) and higher oil (20%), although both formulations resulted better oral bioavailability in rats than marketed suspension (Chudasama et al, 2015). From all these discussed studies, it can be concluded that the in vitro models, undoubtedly can give idea about drug absorption through the intestine, but in vivo studies are essential to find out the exact outcome of the delivery system.…”
Section: Correlation Between In Vitro Model and In Vivo Studiesmentioning
confidence: 99%
“…Their purpose is mainly to dissolve lipophilic drugs into liquid formulations or to promote consistent, uniform dispersion into gastrointestinal fluid after oral administration. By including TGs or their derivatives in oral formulations, the intestinal absorption of poorly water-soluble drugs can be improved and the degree of interindividual variation can be reduced. From the oral administration of such medicines, the range of intake of TGs may be a few grams. The dietary intake of fat (TGs) could be more than 50 g per day; however, this amount strongly depends on the individual.…”
Section: Discussionmentioning
confidence: 99%
“…40 Different ratios of surfactants were used to stabilize droplet surfaces with enhanced RAV incorporation capacity. RAV was loaded in F2 (5% Epikuron) at concentrations up to 6 mg/mL, with a significant increase in mean diameter from 215 nm to 247 nm (P,0.05).…”
Section: -21mentioning
confidence: 99%